Amplified Asymmetric Impact of ENSO Events on the Wintertime Pacific‐North American Teleconnection Pattern. Issue 2 (17th January 2023) - Wang, Xueqing; Yang, Xiu‐Qun
Abstract: El Niño/Southern Oscillation (ENSO) as the strongest tropical interannual signature has the most prominent impact on wintertime Pacific‐North American (PNA) teleconnection pattern. ENSO exhibits an increasing asymmetry in recent decades. This study quantifies its extratropical asymmetric impact on the amplitude of the PNA pattern, using a normalized asymmetry index defined as a ratio of asymmetric versus symmetric anomalies for El Niño and La Niña. Relative to the ENSO asymmetry, the extratropical asymmetric impact is largely amplified especially downstream by up to 82%. Such an amplification is attributed to noticeable increases, 83.6% (68.9%), in asymmetry of Rossby wave source (RWS) anomalies over two key regions of North Pacific, in which anomalous divergence induced by nonlinear condensational heating feedback and anomalous synoptic eddy forcing are two major contributors. The former contributes 39.3% (47.5%) over the western (eastern) North Pacific through increasing asymmetric RWS anomalies, while the latter contributes 29.5% (21.3%) through decreasing symmetric RWS anomalies. Plain Language Summary: El Niño/Southern Oscillation (ENSO) as the strongest tropical interannual signature can cause prominent wintertime North American climate anomalies through Pacific‐North American (PNA) teleconnection pattern. El Niño and La Niña events as two opposite phases of ENSO are not mirror images of each other, with El Niño significantly stronger than La Niña in recent decades, due to the nonlinearities in the tropical air‐sea system. Such an ENSO asymmetry tends to induce El Niño to have more serious impact than La Niña. This asymmetric impact of ENSO events on the PNA pattern is quantitatively found in this study to be largely amplified especially downstream due to the nonlinearities within the extratropical atmosphere, with using a normalized asymmetry index defined as a ratio of the asymmetric versus symmetric anomalies for El Niño and La Niña. The amplification is attributed to noticeable increases in asymmetry of the Rossby wave source anomalies over North Pacific, in which anomalous divergence induced by nonlinear condensational heating feedback and anomalous synoptic eddy vorticity forcing are two major contributors. Given that ENSO is the primary source of seasonal predictability, the amplified asymmetric impact on the PNA pattern discovered in this study would be of predictive value for the North American climate anomalies. Key Points: Relative to the El Niño/Southern Oscillation (ENSO) asymmetry, ENSO's asymmetric impact on the Pacific‐North American pattern is quantitatively found to be largely amplified by up to 82% The amplified asymmetric impact is due to the noticeable increases in asymmetry of Rossby wave source (RWS) anomalies over North Pacific Extratropical nonlinearities in condensational heating and synoptic eddy vorticity feedbacks are responsible for the asymmetric RWS increase